2015
DOI: 10.4172/2155-9899.1000307
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 is Constitutively Activated in the T/C28a2 Immortalized Juvenile Human Chondrocyte Line and Stimulated by IL-6 Plus Soluble IL-6R

Abstract: T/C28a2 immortalized juvenile human chondrocytes were employed to determine the extent to which activation of Signal Transducers and Activators of Transcription-1 (STAT1) occurred in response to recombinant human interleukin-6 (rhIL-6) or rhIL-6 in combination with the soluble IL-6 receptor (sIL-6R). Two forms of STAT1, STAT1A and STAT1B, were identified on SDS-PAGE and western blotting with anti-STAT1 antibody. Western blotting revealed that STAT1 was constitutively phosphorylated (p-STAT1). Although incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…We also showed western blots at Immunology summit-2015 demonstrating that STAT1 was constitutively phosphorylated in the T/C28a2 chondrocyte line [ 16 ]. However, C-28/I2 chondrocytes incubated with rhIL-6 (50 ng/ml) resulted in the phosphorylation of STAT3 without changing total STAT3 [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also showed western blots at Immunology summit-2015 demonstrating that STAT1 was constitutively phosphorylated in the T/C28a2 chondrocyte line [ 16 ]. However, C-28/I2 chondrocytes incubated with rhIL-6 (50 ng/ml) resulted in the phosphorylation of STAT3 without changing total STAT3 [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…We had previously shown using a quantitative immunoblot analysis that rhIL-6, rhTNF-α or sIL-6R activated STAT3 protein in human immortalized chondrocyte cell lines [ 15 , 16 ]. We had also shown that incubating human chondrocytes enzymatically liberated from OA knee cartilage with rhTNF-α (10 ng/ml) resulted in the phosphorylation of U-STAT3 (p-STAT3) without altering total U-STAT3α [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these cells were cultured in specific medium (Invitrogen, Carlsbad, CA, USA) supplemented with 10% (v/v) fetal bovine serum (FBS, Invitrogen), 100 μg/ml streptomycin, and 100U/ml penicillin (Invitrogen) at 37 °C with 5% CO 2 . Cells were serum starved for 12 h prior to EGF (10 ng/ml), insulin (100 nmol/l), TGF-β (5 ng/ml), IL-6 (50 ng/ml), and estradiol (10 nM) treatment for 6 hours36373839. Culture medium was switched to serum-free and phenol red-free medium to avoid potential interference from serum hormones or phenol red.…”
Section: Methodsmentioning
confidence: 99%